In vitro DNA binding properties of VirB, the Shigella flexneri virulence regulatory protein - DORMAN, CHARLES (My University, 2003)
The DNA-binding activity of the Shigella flexneri VirB transcription factor was studied in vitro. The protein was found to bind non-specifically to DNA, but showed preferential binding to VirB-dependent promoter sequences. DNA binding was contingent on the presence of an intact helix-turn-helix motif. While high molecular mass protein–DNA complexes were formed in both specific and non-specific interactions with DNA, mutant derivatives of VirB lacking a leucine zipper domain or a carboxyl-terminal-located oligomerisation domain formed discrete complexes, indicating that an ability to oligomerise on DNA was responsible for the formation of high molecular mass complexes by the wild-type protein.
PUBLISHED
Keywords: Shigella flexneri; Helix-turn-helix motif; Leucine zipper; Gene regulation; Transcription facto; VirB protein; Genes & Society; Immunology, Inflammation & Infection